ANGGARAN DAERAH DAN “FISCAL STRESS” (Sebuah Studi Kasus pada Anggaran Daerah Provinsi di Indonesia) - Abdul Halim (Journal of Indonesian Economy and Business (JIEB), 2001)
This study attempts to empirically compare and analyze the role (proportion) of Actual Local Government Genuine Receipts (Pendapatan Asli Daerah or PAD) on Actual Total Local Government Receipts of Local Government Budget (Anggaran Pendapatan dan Belanja Daerah or APBD). It also analyzes the role of the actual local taxes and local retributions—as the primary sources of PAD—on the PAD. Using the provincial governments, this study performs the comparison due to ―the fiscal stress‖ (i.e., the economic crisis and the launching of new local taxes and retributions in 1997).The 1996/1997 -1998/1999 local government budgets are used as data before and after the fiscal stress occurred. The results show that the fiscal stress generally does not influence the role. When local taxes and retributions are analyzed based on the fiscal stress, the results show that only local retributions are affected